The Feminist Postmodernist Alliance in Lidia Falcón’s Postmodernos (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
In her novel Posmodernos ( 1993),  Lydia Falcon appropriates certain feminist and postmodernist theoretical percepts in order to elaborate her critical discourse.  that social and political security associated with the transition to democracy in the early 1980s it gave way to personnel and social insecurities in the 1990s, the signs of an identity crisis and ideological crisis, respectively. relying on narrative fragmentation,  spatial displacement, and the dissolution of the character,  the Spanish novelist is able to capture the ambivalence and uncertainty of Spain in the last decade of the 20th century. using a technique that combines and artistic postmodernist sensibility with a social and political feminist consciousness, falcon challenges that traditional modes of perception and representation in order to direct us towards something Beyond what was conventionally established and historically propagated